2019
DOI: 10.3390/cells8080922
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Intrinsic and Innate Immunity during HIV Infection

Abstract: Restriction factors are antiviral components of intrinsic immunity which constitute a first line of defense by blocking different steps of the human immunodeficiency virus (HIV) replication cycle. In immune cells, HIV infection is also sensed by several pattern recognition receptors (PRRs), leading to type I interferon (IFN-I) and inflammatory cytokines production that upregulate antiviral interferon-stimulated genes (ISGs). Several studies suggest a link between these two types of immunity. Indeed, restrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 288 publications
(379 reference statements)
2
30
0
2
Order By: Relevance
“…Several genes have been identified as encoding potential PRRs for retroviruses, and the overall diversity of retrovirus PRRs has been reviewed elsewhere [ 39 , 40 , 41 ]. These studies have revealed a diverse set of retrovirus sensing pathways that respond to a variety of retrovirus-associated molecules–including both viral genomic RNA, reverse transcribed viral DNA, viral proteins, as well as non-viral molecules associated with retroviral particles.…”
Section: Innate Sensing Receptors For Retrovirusesmentioning
confidence: 99%
“…Several genes have been identified as encoding potential PRRs for retroviruses, and the overall diversity of retrovirus PRRs has been reviewed elsewhere [ 39 , 40 , 41 ]. These studies have revealed a diverse set of retrovirus sensing pathways that respond to a variety of retrovirus-associated molecules–including both viral genomic RNA, reverse transcribed viral DNA, viral proteins, as well as non-viral molecules associated with retroviral particles.…”
Section: Innate Sensing Receptors For Retrovirusesmentioning
confidence: 99%
“…In addition to providing a first line of defence against pathogen infection, innate immune responses are pivotal in priming the adaptive immune responses through the induction of antigen specific T cell activation and promotion of humoral immunity. Thus, understanding mechanisms by which the innate immune system recognizes and responds to HIV will be instructive in the design of HIV-1 vaccines and/or adjuvants [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…To date, multiple families of PRRs have been implicated as sensors responsible for detecting HIV-1 infection, which include toll-like receptors (TLRs), RIG-I-like receptors (RLRs), and cytosolic DNA sensors (Table 1) [16,[22][23][24]. The mechanistic details for initiation and regulation of HIV-1 innate sensing have been extensively studied, but remain controversial regarding the PAMP, innate sensors, and regulators involved in physiologically-relevant sensing processes [9,10,25]. Moreover, HIV-1 has evolved elaborate strategies to circumvent immune surveillance and response.…”
Section: Introductionmentioning
confidence: 99%
“…These have been termed restriction factors and constitute the so-called intrinsic immunity, which is now considered to be the third arm of immunity [ 1 ]. Most restriction factors, however, even if they are constitutively expressed, are upregulated by type I interferon(s), and thus intrinsic defenses can be considered to be a part of antiviral innate immunity [ 2 , 3 ]. Since the discovery of the first HIV-1 restriction factor, in 2002, APOBEC3G [ 4 ], many other factors have been identified and shown to inhibit nearly all steps of the HIV-1 replicative cycle (reviewed in [ 5 , 6 , 7 ]).…”
Section: Introductionmentioning
confidence: 99%